The barriers of undergraduate university students between medical vs. nonmedical courses to perform physical activity: cross-sectional study - Kamsani, Nurain Natsha Binti; Bhat, Ishfaq Bashir (Longdom Publishing SA, 2023)
ABSTRACT Background: More than 80% of the adult population globally spent their time developing sedentary lifestyle behavior rather than being physically active. University students were recorded to be more likely to adopt sedentary lifestyle behavior. This study aims to identify the barriers of undergraduate students of International Islamic University Malaysia (IIUM) from engaging in physical activity and the associations of each barrier with different fields of study (medical vs. non-medical courses). Objectives: To identify the barriers to physical activity faced by undergraduate medical vs. non-medical related courses students of IIUM associations between each barrier with different field of study. Study design: Cross-sectional study involving undergraduate IIUM students. Method: A set of questions from the Centre for Disease Control and prevention (CDC) entitled 'barrier to being active quiz' was used to investigate the physical activity behavior among university students. The questionnaire was presented in google form and non-probability sampling method, specifically the convenience sampling method was used for this study. Results: ‘Lack of willpower’ was the main barrier to physical activity with percentage 72.1% compared to others. Comparison in frequencies of days performing physical activity also shows that medical related course students involving more compared to non-medical related course students. Then, the Chi-square test of independence was used to identify the association between each barrier in ‘barrier to being active quiz’ with different fields of study. Only ‘fear of injury’ appears to have a significant association between both of the variables (p=0.033). Conclusion: This study shows that the main barrier to physical activity among medical courses and non-medical courses undergraduate IIUM students' is ‘lack of willpower’. Although ‘lack of time’ was not listed as the main barrier for undergraduate IIUM, more than half of the respondents still cannot manage their time properly for Physical Activity (PA). For the comparison between different field of study and involvement in PA, it shows that there was no significant difference in both groups.